Implementation of The Consignment System at Lucky Jaya Mart Store: A Review of Islamic Business Ethics - Hakim , Lukmanul; Amalia , Septia Tri (Al-Insyiroh: Jurnal Studi Keislaman, 2023)
This study aimed to determine how the Lucky Jaya Mart store carried out the business behavior towards its business partners and the implementation of the consignment sales system with the three product consignors of different categories of goods entrusted and reviewed according to Islamic Business Ethics. Using observation and interviews with Lucky Jaya Mart store, the consignor of chips products, the consignor of accessories and children's toys products, and the consignor of sweetbreads products as research data. The researcher used a qualitative approach with literature studies on relevant scientific works to analyze the business activities carried out by the Lucky Jaya Mart store. Based on the study results, Lucky Jaya Mart store had done business well. All activities were considered ethical regarding conducting business using a consignment sales system and the relationships between people involved. There were no parties who felt aggrieved in this collaboration system. On the contrary, all parties involved felt their rights and obligations were fulfilled so that ongoing business relationships could occur harmoniously.